The role of telomerase reverse transcriptase (TERT) promoter mutations in prognosis in bladder cancer. Issue 1 (1st January 2021) - Wan, Song; Liu, Xuan; Hua, Wei; Xi, Ming; Zhou, Yulin; Wan, Yueping
ABSTRACT: Telomerase reverse transcriptase (TERT) promoter mutations have been recognized as a common genetic event in bladder cancer (BC). Many studies have found the high TERT promoter mutations' prevalence in BC recurrence patients which may make the TERT promoter mutations become a potential prognosis prediction of BC. We performed a systematic search in Embase, PubMed, and Web of Science in January 2021. The aspects of evaluation, methods, validation, and results were used to evaluate the included studies' quality. We reviewed two of the most common mutations in types of TC, C288T and C250T and their relationship with prognosis of BC. Eight studies contained 1382 cases were enrolled in our study. The percentage of TERT promoter mutations in these cases was 62.5%. A statistically significant association was detected between TERT promoter mutation and recurrence (HR: 2.03, 95% CI: 1.53–2.68, p < 0.001). However, TERT promoter mutation was not significant associated with overall survival (HR: 1.077, 95% CI: 0.674–1.718, p = 0.757). No significant heterogeneities were observed (I 2  = 47.5%, P = 0.064; I 2  = 58.7%, p = 0.120, respectively). Bladder cancer patients with TERT promoter mutations take a higher risk of recurrence. TERT promoter mutations may become a potential prediction factor for bladder cancer recurrence. GRAPHICAL ABSTRACT: uf0001